Strengthening urban producer organizations for innovative vegetable production and marketing in West African cities: experiences from Accra, Chana and Ibadan, Nigeria - Larbi, Theophilus Otchere; Cofie, Olufunke O.; Amoah, Philip; Veenhuizen, René van (2014)
Urban and peri-urban agriculture (UPA) is seen as a subsistence-oriented production system. It has been given little formal support or recognition by city authorities in the development plans. Recent development programmes have continued to raise awareness about this phenomenon, and local authorities have begun to understand the role UPA can play in improving urban food supply and reducing poverty. Constraints to UPA such as limited access to land and good quality water, poor farmer organization, participation in policy development, and poor policy support, imply that UPA needs to be productive and profitable through diverse innovations. In Accra, Ghana and Ibadan, Nigeria, 200 urban farmers were organized into 8 producer groups and trained using technical and organizational innovations in vegetable production so as to improve yield and income. The Ibadan groups were predominantly female farmers, while Accra groups were mainly male. Training was delivered through the Urban Producer Field Schools (UPFS) on topics ranging from integrated plant production and protection principles, food safety and risk-minimization in wastewater use for irrigation to value-addition for marketing. Farmers dealt with organized marketing, targeting niche markets. The farmer groups in Accra progressed significantly over a one-year period of group strengthening as became evident in their organized structure and participation in group processes. The Ibadan group lagged behind at the group formation stage, apparently because of the hierarchical nature of the group and personal conflicts. In addition, external factors such as disease infestation affected the group processes in Ibadan. Adoption of innovations was higher among the farmers in Accra, where farmers applied at least 3 out of 6 different innovations, while adoption of innovations among female farmers in Ibadan was low: as less than 30% adopted 2 out of 5 different innovations. In both Accra and Ibadan, considerable improvement in crop performance was recorded.